"Everything Just Went Apeshit": Revisiting the "Mobilization Model" of Journalistic Impact. (9th December 2020) - Konieczna, Magda; Graves, Lucas
ABSTRACT: On 5 April 2016, Iceland's prime minister became the first high-profile casualty of the Panama Papers investigations published around the world two days earlier, stepping down after reports of his family's hidden offshore wealth triggered massive public protests. The resignation was widely hailed as a demonstration of the power of investigative or "accountability" reporting to activate democratic citizens and effect real-world change. This paper reconstructs the Panama Papers reporting in Iceland as an important new case study in the growing literature on the impacts of journalistic revelations. Drawing on in-depth interviews, we ask what this dramatic case tells us about how major exposés produce political outcomes, as well as how the journalists involved understood the potential impacts of their work. We show that even in what looks like a clear-cut case of the so-called "mobilization model"—where change results from the public's response to a story—more complex dynamics are at work: Reporters worked actively to maximize the impact of their work, understanding these efforts in terms of its inherent newsworthiness, and the ultimate outcome of the revelations was shaped by a cycle of interactions between media and political actors that began well before publication.